Probiotics as Promising Immunomodulatory Agents to Prevent COVID-19 Infection: A Narrative Review - Adnan, Muhammad Luthfi; Pramaningtyas, Miranti Dewi (International Journal of Medical Students, 2020)
After the outbreak in December 2019, Coronavirus Disease (COVID-19) has become a global health problem because of its rapid spread throughout the world. To date, there are no effective therapies to treat or prevent COVID-19 infection. Probiotic bacteria are widely used to prevent gastrointestinal infections by modulating intestinal microbiota. Therefore, this literature review focuses on the potential possessed by probiotic bacteria for the prevention of future COVID-19 infections. Information was extracted from PubMed and Google Scholar using the keywords: "COVID-19", "immunomodulator", "inflammation", and "probiotic" and synthesized into this narrative review. The results showed that probiotic bacteria have immunomodulatory activity that can increase immunity against pathogens by regulating the immune system through modulation of intestinal microbiota and interactions with the lymphatic system in the digestive tract. The ability of the immune system regulation by probiotic bacteria has the effect of increasing the body's defense mechanisms against pathogens that infect the respiratory tract. However, further evidence is still needed regarding the effect of probiotic immunomodulators in combating future COVID-19 infections.